Исследование закритического поведения ортотропных пологих оболочек сложной формы в плане - Курпа, Лидия Васильевна; Любицкая, Екатерина Игоревна (НТУ "ХПИ", 2006)
Geometrically nonlinear behavior of orthotopic shallow shells subjected to the transverse load is investigated. The method of linearization of nonlinear equations and finding of upper and lower critical load, which is based on the combination of variational methods and R-function theory, is proposed. The algorithm is applied to solve problems of orthotopic spherical shallow shells with complex plan form. Test results of isotropic case are compared with those available in the literature
Keywords: решение нелинейных краевых задач; теория R-функций; дифференциальные уравнения; изотропный материал